Efficacy of levetiracetam, lamotrigine and sodium valproate on seizure attacks and EEG disorders in patients with juvenile myoclonic epilepsy: A double blind randomized clinical trial - Sajjad Daneshyar; Masoud Ghiasian; Sahar Moradi; Elham Khanlarzadeh (Babol University of Medical Sciences, 2022)
Background: Juvenile myoclonic epilepsy (JME) is one of the most important types of generalized idiopathic epilepsy. Patients generally respond quickly and perfectly to standard antiepileptic drugs but lifelong medication is necessary. Sodium valproate is the drug of choice in most references but it has some adverse reactions and some patients cannot tolerate the complications. Because of the need for life long treatment in this young aged group particularly child bearing women, we aimed to analyze the efficacy of these drugs to determine which has better efficacy with lower adverse effects. Methods: In this double-blind clinical trial 102 patients suffering from juvenile myoclonic epilepsy were randomly divided to three groups and treated with valproate, levetiracetam or lamotrigine and followed for 12 months at specified intervals. Results: Patients' mean age was 22.8 years and 28.4% of them were males and 71.6% were females. Effective terminal dose of sodium valproate, levetiracetam and lamotrigine were 1000, 1000 and 250mg, respectively. The rate of failure in controlling seizures and myoclonic jerks in lamotrigine group was meaningfully more than levetiracetam and sodium valproate (P=0.037).The general side effects of sodium valproate were much more; but there was not any significant difference between their effects on electroencephalogram (EEG) findings (P=0.81). Conclusion: Levetiracetam and sodium valproate have similar efficacy. But in the group of lamotrigine, rate of failure, myoclonus and drug adverse reactions were meaningfully more than sodium valproate and levetiracetam. According to our study, lamotrigine could not be a suitable treatment option for JME patients as a mono therapy. Levetiracetam can be a good alternative to sodium valproate, especially in women of childbearing age